2013
DOI: 10.1080/03235408.2013.809224
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of stem rot of groundnut (Arachis hypogaeaL.) caused bySclerotium rolfsiiSacc. with actinomycetes

Abstract: A total of 30 isolates of actinomycetes were isolated from the rhizosphere soils of groundnut collected from different parts of Tamil Nadu, India and tested for their inhibitory activity against Sclerotium rolfsii Sacc., the stem rot pathogen of groundnut. Among the various isolates tested in vitro, five isolates (CBE, MDU, PDK, ANR and SA) were found effective in inhibiting the mycelial growth of S. rolfsii in dual culture assay. These isolates were identified as Streptomyces sp. on the basis of standard bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Actinobacterial isolate Actino 48 more effectively inhibited mycelia growth of S. rolfssii than other actinobacterial isolates. These results agree with those obtained by Adhilakshmi et al [39], who reported that Streptomyces sp. MDU most effectively inhibited the growth of S. rolfsii.…”
Section: Discussionsupporting
confidence: 93%
“…Actinobacterial isolate Actino 48 more effectively inhibited mycelia growth of S. rolfssii than other actinobacterial isolates. These results agree with those obtained by Adhilakshmi et al [39], who reported that Streptomyces sp. MDU most effectively inhibited the growth of S. rolfsii.…”
Section: Discussionsupporting
confidence: 93%
“…46 Bacillus subtilis and Streptomyces cellulosae have been proven to decrease the peanut pod rot disease caused by Fusarium solani and Sclerotium rolfsii. 47,48 Microplastics could act as a reservoir and shelter for soil pathogens, causing a negative effect on beneficial bacteria present in soil and increasing the risk of plant infection by soil-borne diseases. 49,50 In our study, the relative abundance of Bacillus subtilis and Streptomyces cellulosae in the geocarposphere soil was reduced with microplastic contamination, but induced by biochar application.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in some specific taxa of soil bacteria often positively correlated with soil‐borne disease suppression 46 . Bacillus subtilis and Streptomyces cellulosae have been proven to decrease the peanut pod rot disease caused by Fusarium solani and Sclerotium rolfsii 47,48 . Microplastics could act as a reservoir and shelter for soil pathogens, causing a negative effect on beneficial bacteria present in soil and increasing the risk of plant infection by soil‐borne diseases 49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…The cultivars were grouped into group 1 (resistant), group 2 (moderately resistant), group 3 (susceptible) and group 4 (highly susceptible cultivars) based on percent disease incidence (PDI) in groundnut cultivars. The pathogen namely Sclerotium was isolated from the infected stem regions of groundnut through tissue segmentation method (Adhilakshmi et al, 2014) from Aliyar, Coimbatore, Sivaganga and Madurai region.…”
Section: Survey and Stem Rot Pathogenmentioning
confidence: 99%